PENGARUH IKLIM KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMK NEGERI 1 KOTA JAMBI - Benar Sembiring, Yahya Purnama, (SJEE (Scientific Journals of Economic Education), 2017)
This study aims to determine the picture of work climate, work motivation, and teacher performance in SMK Negeri 1 Kota Jambi, and the influence of work climate and work motivation on teacher performance in SMK Negeri 1 Kota Jambi. The results showed that (1) Work climate and work motivation of teachers in SMK Negeri 1 Kota Jambi is good. (2) Work climate has significant effect on teacher performance in SMK Negeri 1 Kota Jambi. (3) Work motivation has a significant effect on teacher performance in SMK Negeri 1 Kota Jambi.Kata Kunci : Working Climate, Work Motivation, Teacher Performance